The Effect of Leadership Style on Employee Motivation of PT. Anugrah Argon Medica, Jakarta Timur - Danang D Susilo (Institute of Computer Science (IOCS), 2021)
Good leadership style the level of employee work motivation will increase. Giving motivation is the most important thing in a person's leadership, a good leader will always provide encouragement that motivates his employees to increase employee motivation. This study aims to determine the effect of leadership style on employee motivation at PT Anugrah Argon Medica. This study used a population of 28 employees with a sample of 26 respondents, data collection techniques using a questionnaire. The data analysis technique used is product moment correlation coefficient test, determination coefficient test and regression equation test with SPSS v20 data processing. Based on the calculation of the correlation coefficient, the value of 0.656 shows that the level of a strong relationship between leadership style and motivation, the coefficient of determination shows a value of 43%, indicating that the influence of leadership style on motivation is 43% and the remaining 57% is influenced by other factors that require research. Furthermore. Based on SPSS, the regression value of constant (a) is 64.357, while the value of leadership style (b) is 0.174, so the regression equation can be written as Y = 64.357 + 0.174X, a constant of 64.357 states that if the leadership style is 0, then motivation level of 64.357. While the X regression coefficient of 0.174 states that each additional value of leadership style is 1, the motivation value will increase by 0.174. Based on the hypothesis test, the t value is 2.181> 2.055, where the t value> from the t table, then Ho is rejected and Ha is accepted, that is, there is an influence of leadership style on employee work motivation.